Patient Specific Three-Dimensional Implant for Reconstruction of Complex Mandibular Defect. Issue 4 (June 2019) - U, Vignesh; Mehrotra, Divya; Howlader, Debraj; Singh, Praveen Kumar; Gupta, Sneha
Abstract : Abstract: This study was planned to evaluate the improvement in mandibular function, facial esthetics and quality of life after reconstruction of complex mandibular defects using patient-specific three-dimensional (3D) titanium implant. A total of 7 patients, who visited our outpatient clinic for reconstruction of mandibular defects after removal of their primary mandibular lesion and refused treatment with autologous bone grafts were treated with patient-specific implant for reconstruction of mandible. Three-dimensional virtual treatment planning was carried out using their 3D computed-tomographic data. The unaffected contralateral side of mandible was superimposed on the defect side and a customized implant was designed in the desired size and shape on the virtual model using computer aided designing and milled in titanium using selective laser melting, for precise anatomic mandibular reconstruction. There was significant improvement in their esthetics, function, and quality of life. The symmetry of the face and occlusion was restored with adequate mouth opening, closing, and lateral movements of the mandible with no deviation of jaw during movements. The patient specific implants appear to be very useful for precise reconstruction of mandible with greater accuracy. The concept of using customized implant with the help of 3D virtual treatment planning, stereolithographic models and computer aided designing greatly improves mandibular restoration and helps to achieve good facial profile, aesthetics and dental rehabilitation preventing severe complications related to autologous grafts.